2004
DOI: 10.1161/01.cir.0000146378.65439.7a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fosinopril and Pravastatin on Cardiovascular Events in Subjects With Microalbuminuria

Abstract: Background-Microalbuminuria is associated with increased risk of cardiovascular events. We assessed whether therapeutic intervention aimed at lowering urinary albumin excretion would reduce cardiovascular events in microalbuminuric subjects (15 to 300 mg/24 hours). Methods and Results-From the Prevention of Renal and Vascular Endstage Disease (PREVEND) cohort (nϭ8592), 1439 subjects fulfilled the inclusion criteria of the PREVEND Intervention Trial (PREVEND IT). Of these subjects, 864 were randomized to fosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
2
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 474 publications
(140 citation statements)
references
References 25 publications
0
127
2
8
Order By: Relevance
“…This probably contributes to the inconsistent relationship in studies between cholesterol-lowering therapy and cardiovascular outcome in chronic kidney disease. [32][33][34][35][36][37][38][39][40] In a more recent meta-analysis, statin therapy reduced the risk of first major vascular event by 21% (RR 0.79, 95% CI 0.77-0.81) per mmol/L reduction in LDL cholesterol. Smaller relative effects on major vascular events, major coronary events and vascular mortality were observed as GFR declined.…”
Section: Articlementioning
confidence: 99%
“…This probably contributes to the inconsistent relationship in studies between cholesterol-lowering therapy and cardiovascular outcome in chronic kidney disease. [32][33][34][35][36][37][38][39][40] In a more recent meta-analysis, statin therapy reduced the risk of first major vascular event by 21% (RR 0.79, 95% CI 0.77-0.81) per mmol/L reduction in LDL cholesterol. Smaller relative effects on major vascular events, major coronary events and vascular mortality were observed as GFR declined.…”
Section: Articlementioning
confidence: 99%
“…32 Digoxin toxicity may result from deteriorating renal function or dehydration, with symptoms most commonly including nausea, vomiting and drowsiness. 33 Digoxin may also be useful for rate control in the treatment of atrial fibrillation in heart failure.…”
Section: Digoxinmentioning
confidence: 99%
“…This has already been shown in subjects with macroalbuminuria. However, it was recently shown that lowering of albuminuria with an ACE inhibitor in subjects with an elevated albuminuria (15–300 mg/day) was also associated with fewer CV events, especially in subjects with an albumin loss in the range of 50–300 mg/day [31]. …”
Section: Microalbuminuria – a Marker Of CV Eventsmentioning
confidence: 99%